Conducta obstétrica en primigesta de 29 años de edad con embarazo ectópico ovárico de 5,5 semanas - Mosquera Espinoza, Mirian Marlene (2021)
SUMMARY The case presented was the obstetric behavior to be followed in a 29-year-old patient with an accident ectopic pregnancy of 5.5. weeks of gestation which presented the admission to the emergency area with pain in the right iliac fossa of great intensity of + - 36 hours of evolution progressively in the last 8 hours with amenorrhea of 2 months where it presented a couple of days ago scarce bleeding upon arrival at the unit for moderate bleeding, clinical diagnosis was made by ultrasound resulting in a ruptured left ectopic, surgery was performed where the product was extracted with a gestational age of + - 5.5 weeks and follow-up is carried out periodical by external consultation and with indication of changes of habits as an important mention.